A Compliance Evaluation System for Broadcasting Institutions in the Post-Analog Transition Era: Applying AHP and SAW to Administrative, Technical, and Legal Criteria - Trianthono, Indra; Salim, Ravi Ahmad (Universitas Dr. Soetomo, 2025)
This study addresses the pressing need for systematic compliance evaluation of radio broadcasting institutions in Indonesia amid the country's transition to digital broadcasting. As the Ministry of Communication and Information Technology mandates adherence to new regulatory frameworks, ensuring broadcaster compliance has become critical for maintaining media accountability, quality, and governance. To evaluate compliance across administrative, technical, and legal dimensions, this study integrates the Analytic Hierarchy Process (AHP) to determine priority weights and the Simple Additive Weighting (SAW) method to rank 527 radio broadcasters. The AHP method achieved a consistency ratio (CR) of less than 0.1, validating expert-based weight assignments for eight regulatory criteria, including licensing, permit payment, technical equipment standards, and ownership reporting. The SAW method then translated these weights into performance scores, categorizing stations into three compliance levels: High (382 providers, with an average score of 100%), Moderate (120 providers, with an average score of 83.65%), and Low (25 providers, with an average score of 50.85%). These results indicate a relatively high regulatory compliance among radio broadcasters, suggesting improved institutional awareness and the effectiveness of current oversight mechanisms. A data-driven Decision Support System (DSS) developed from this framework offers regulators a scalable tool for formulating targeted policies and interventions based on measurable compliance outcomes.